For the many: permitting deceased donor kidney transplantation across low‐titre blood group antibodies can reduce wait times for blood group B recipients, and improve the overall number of 000MM transplants ‐ a multicentre observational cohort study. (21st January 2019) - Manook, Miriam; Mumford, Lisa; Barnett, Alec Nicholas R.; Osei‐Bordom, Daniel; Sandhu, Bynvant; Veniard, David; Maggs, Tim; Shaw, Olivia; Kessaris, Nicos; Dorling, Anthony; Shah, Sapna; Mamode, Nizam
Summary: Blood group O or B recipients wait longer for a kidney transplant. We studied the distribution of anti‐ABO blood group antibody titres in patients awaiting a kidney transplant, and modelled the effect of altering the UK National Kidney Allocation Scheme to allow for patients with 'LOW' titres (≤1:8, ≤3 dilutions) to receive a deceased donor ABOi (ddABOi) transplant. In a prospective study of 239 adult patients on the waiting list for a transplant in 2 UK centres, ABO‐antibody titres (anti‐A and anti‐B) were measured. Based on the proportions of 'LOW' anti‐A or anti‐B antibodies, four simulations were performed to model the current allocation rules compared with variations allowing ddABOi allocation under various conditions of blood group, HLA matching, and waiting time. The simulations permitting ddABOi resulted in more blood group B recipients being transplanted, with median waiting time reduced for this group of recipients, and more equitable waiting times across blood groups. Additionally, permitting ddABOi resulted in greater numbers of 000MM allocations overall in compatible transplants under modelled conditions. Changing allocation in the UK to permit ddABOi in patients with 'LOW' titres would not change the total number of transplants, but redistributes allocation more equitably amongst blood groups, altering waiting times accordingly.